Utilization of Interactive Multimedia in Science Learning at Junior High School MTs N 7 - Rizki Amalia Fatma; Andini Ika Saputri; Ika Surya Yunita; Dewi Nurul Istiqomah (Universitas Ahmad Dahlan, 2023)
Science learning at junior high school level plays an important role in providing students with a good understanding of complex biological concepts. However, conventional learning approaches limited to the use of textbooks and lectures are often less interesting for students and less effective in facilitating their learning. This research aims to explain how the utilization of interactive multimedia can improve science learning at MTs N 7 Sleman. In addition, this study also discusses the role of interactive multimedia in facilitating collaborative learning in the classroom along with the tools applied. The type of research used in this study is qualitative with a descriptive approach. The technique used in data collection uses semi-structured interview techniques conducted virtually using the Google meet platform. By applying interactive multimedia in Biology learning at MTs N 7 Sleman, it is expected that students can be more involved, enthusiastic, and gain a better understanding of Biology concepts. This will help improve the quality of education at MTs N 7 Sleman and prepare students to face the challenges of science and technology in the future.